Study of Axillary and Oral Temperature in A Group of Young Adult and Children (Journal of Medicine, 2008)
Background: In comparison to other bedside clinical examination basal body temperature is one of the most important indicators in establishing diagnosis of disease. Some time physiological alteration is also important and it should be kept in mind. Materials and Methods: A total number of 246 cases were included in this study irrespective of their age and sex. This observational study was done in Mymensingh Medical College (a tertiary level institute) where study population was medical student. Materials also collected from a district orphanage. Results: There were no significant difference in oral temperature between young adult and children. And also no significant difference of axillary and oral temperature between male and female children. Conclusion: In this observational study there were no significant temperature difference between oral and axillary region irrespective of age and sex. Â  DOI = 10.3329/jom.v9i2.1435 J MEDICINE 2008; 9 : 78-81